Sistem Pelayanan Reservasi dan Diagnosa Penyakit Kucing Menggunakan Metode Certainty Factor Berbasis Web - Nadilla, Baiq Yulia; Andriska Candra Permana, Baiq; Sudianto, Aris (Fakultas Teknik Universitas Hamzanwadi, 2024)
According to research in 2018, 47% of Indonesia's population keeps cats. This proves that almost half of Indonesia's population chooses to keep cats. But without us realizing it, cat owners don't fully understand how to properly care for cats and even some people are still wrong in giving medication when cats are unwell, as a result many cats experience death due to inaccuracies in providing first aid. One of the pet shops that provide consulting services is WIBI Petshop. WIBI Petshop is a pet shop that is busy with customers. This pet shop offers many services ranging from grooming services, hotel or daycare services to consulting services. WIBI Petshop also sells various kinds of pet needs. Currently WIBI Petshop is one of two pet shops in Selong whose services are still manual. Where a customer who wants to do a consultation must confirm the existence of a veterinarian first, if the doctor is in place, then he can proceed with the consultation, but if not, the customer is forced to return and come the next day to confirm the doctor's presence again. From these problems a solution emerges that can make it easier for customers who want to carry out consultations and make it easier for pet shops to accept consultations submitted by customers. Stages of research on the system will be made using the Certainty Factor method. The purpose of this study was to produce a web-based system for ordering reservation services with the booking feature and being able to check for pet cat diseases through the provided diagnostic page. The author hopes that the system created can carry out the process of ordering services and can diagnose cat diseases to make it easier for cat keepers through the built web. Keywords: pet shop, cat disease reservation and diagnosis, expert system